A more accurate relationship between serum androgen and metabolism among healthy, nonobese, reproductive-age women based on liquid chromatography-tandem mass spectrometry - Sha Ye; Yepei Huang; Yi Lu; Xiaoyan Li; Meiling Ye; Hongyu Lu; Junhua Shi; Jian Huang; Hong Cai (Endocrine Journal)
This study explored a more precise association between androgens and glycolipid metabolism in healthy women of different ages. Body mass index (BMI), waist circumference (WC), and waist-to-hip ratio were used as body fat indicators. High-density lipoprotein (HDL), low-density lipoprotein, triglycerides, and total cholesterol were used as lipid markers. Fasting blood glucose (FBG), fasting insulin, and the homeostatic model assessment of insulin resistance were used to assess insulin resistance and glucose metabolism. Liquid chromatography-tandem mass spectrometry was used to measure androgen indicators, including testosterone, sex hormone-binding globulin (SHBG), free testosterone (FT), dihydrotestosterone (DHT), androstenedione (A4), dehydroepiandrosterone (DHEA), and dehydroepiandrosterone sulfate (DHEAS). DHEAS levels varied across age groups. Correlation analyses with Spearman’s coefficient showed that the free androgen index correlated positively with WC (p = 0.040), FT correlated positively with BMI (p = 0.033) and WC (p = 0.049), SHBG correlated positively with HDL (p = 0.013), and A4 correlated positively with FBG (p = 0.017). Multiple linear regression analysis showed that among healthful women aged 36–40 years, A4 increased with FBG, and SHBG increased with HDL. Even within healthy, nonobese women, lipid and glucose metabolism were robustly correlated with androgens. Yearly metabolic assessments are necessary, particularly for FBG and HDL, since these markers can predict the likelihood of hyperandrogenemia, enabling timely interventions.